2019
DOI: 10.1101/664839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of variations in human P450 oxidoreductase on the aromatase activity of CYP19A1 polymorphisms R264C and R264H

Abstract: Aromatase (CYP19A1) converts androgens into estrogens and is required for female sexual development and growth and development in both sexes. CYP19A1 is a member of cytochrome P450 family of heme-thiolate monooxygenases located in the endoplasmic reticulum and depends on reducing equivalents from the reduced nicotinamide adenine dinucleotide phosphate via the cytochrome P450 oxidoreductase coded by POR. Both the CYP19A1 and POR genes are highly polymorphic, and mutations in both these genes are linked to disor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…The CYP19A1 gene encodes an aromatase that catalyzes the conversion of testosterone and androstenedione to estrone and estradiol. Aromatase, also known as estrogen synthase, is expressed in endometrial cancer, breast cancer, endometriosis and uterine leiomyoma, and its overexpression is related to the occurrence and development of these diseases [27]. Among the top 15 targets, PIK3CA, AKT1, EGFR and AKT2 were reported to be related to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP19A1 gene encodes an aromatase that catalyzes the conversion of testosterone and androstenedione to estrone and estradiol. Aromatase, also known as estrogen synthase, is expressed in endometrial cancer, breast cancer, endometriosis and uterine leiomyoma, and its overexpression is related to the occurrence and development of these diseases [27]. Among the top 15 targets, PIK3CA, AKT1, EGFR and AKT2 were reported to be related to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The increase obtained in the aromatase activity in the presence of imidacloprid and thiacloprid, even if not statistically significant, can be interesting to be further investigated. Indeed, these two compounds could directly act on aromatase as allosteric activators or they could exert their action indirectly on CPR that has an essential role in catalysis and acts as an effector on human aromatase conformation [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Henceforth, our group started to study how these common variants could affect the healthy carriers without an evident phenotype, especially at the level of drug metabolism. Previous studies of our group have shown that polymorphisms in POR can alter the enzymatic activities of its redox partners [6,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 90%
“…Activities of CYP17A1 and CYP19A1 were measure with WT or P228L variant of POR using methods described in detail in our previous publications [14, 18, 20, 21, 30, 40, 44, 45].…”
Section: Methodsmentioning
confidence: 99%